INDEPENDENCE OF BANK INDONESIA POST LAW NO. 4 OF 2023 ON DEVELOPMENT AND STRENGTHENING OF THE FINANCIAL SECTOR - Indrawati, Yuli (Journal of Central Banking Law and Institutions, 2025)
Economic conditions following the COVID-19 pandemic have impacted the financial sector’s condition. Considering how vital the financial sector is for both the economy and people’s lives, the government has enacted the Law on Development and the Strengthening of the Financial Sector (Law on P2SK), which amended and/or repealed several regulations related to the financial sector, including changes affecting Bank Indonesia. The Law on P2SK stipulates that Bank Indonesia is an independent state institution with the authority to carry out its mandate, free from interference from the government and/or other parties, except for some issues expressly regulated by this law. The phrase “except for certain matters which are expressly regulated by this law” means there is a potential threat to BI’s independence. For this reason, it is necessary to study further the implications of the regulations in the P2SK Law on BI’s independence. The benchmarks are institutional, organisational, political, and financial independence. The research method that was used was doctrinal. The results show that under the Law on P2SK, there is a change in the level of autonomy from the institutional, functional, and organisational standpoints. These changes will indeed affect BI’s ability to achieve its goals.